2021
DOI: 10.3389/fendo.2021.686818
|View full text |Cite
|
Sign up to set email alerts
|

Novel AQP2 Mutations and Clinical Characteristics in Seven Chinese Families With Congenital Nephrogenic Diabetes Insipidus

Abstract: ObjectiveMutations in AQP2 (aquaporin-2) lead to rare congenital nephrogenic diabetes insipidus (NDI), which has been limitedly studied in Chinese population.MethodsTwenty-five subjects from seven families with NDI in a department (Beijing, PUMCH) were screened for AQP2 mutations. Clinical characteristics were described and genotype-phenotype correlation analysis was performed.ResultsWe identified 9 AQP2 mutations in 13 patients with NDI, including 3 novel AQP2 mutations (p.G165D, p.Q255RfsTer72 and IVS3-3delC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Although the molecular mechanisms of Liddle syndrome are well-studied and amiloride is used as an effective therapy against the significant hypertension that many patients suffer from, it has been found that not all patients respond the same way to this therapy which leaves them susceptible for hypertension-induced risks ( Pradervand et al, 1999 ). NDI is a more prevalent disease and novel mutations have been discovered recently ( Gao et al, 2020 ; Li et al, 2021 ). However, these studies suggest that some mechanisms of, e.g., AQP2 trafficking remain to be unveiled ( Olesen and Fenton, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms of Liddle syndrome are well-studied and amiloride is used as an effective therapy against the significant hypertension that many patients suffer from, it has been found that not all patients respond the same way to this therapy which leaves them susceptible for hypertension-induced risks ( Pradervand et al, 1999 ). NDI is a more prevalent disease and novel mutations have been discovered recently ( Gao et al, 2020 ; Li et al, 2021 ). However, these studies suggest that some mechanisms of, e.g., AQP2 trafficking remain to be unveiled ( Olesen and Fenton, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the insertion of AQP2 in the apical plasma membrane, which is responsible for water reabsorption ( Hj and Th, 2016 ; Ouyang et al, 2020 ). Dysregulation of AQP2 is closely associated with several clinical disorders characterized by disturbances in body water balance, including congenital nephrogenic diabetes insipidus ( Li Q. et al, 2021 ), lithium-induced nephrogenic diabetes insipidus, electrolyte disturbances, acute and chronic renal function failure, ureteral obstruction, nephrotic syndrome, congestive heart failure, and liver cirrhosis ( Kwon et al, 2013 ).…”
Section: Classification Of Aqps and Their Involvement In Different Pa...mentioning
confidence: 99%
“…Diabetes Insipidus, characterized by excessive water loss, is one of the best studied diseases in this context. Approximately 250 mutations in the AVPR2 gene have been found to explain nearly 90% of human Congenital Nephrogenic Diabetes Insipidus (cNDI), with the remaining 10% attributed to mutations in AQP2 ( Bichet and Bockenhauer, 2016 ; Peng et al, 2019 ; Li et al, 2021 ). As a result, collecting ducts do not reabsorb water as they should.…”
Section: Introductionmentioning
confidence: 99%